Exploited, undervalued - and essential: Domestic workers and the realisation of their rights - Darcy du Toit (Pretoria University Law Press (PULP), 2013)
Exploited, undervalued - and essential: Domestic workers and the realisation of their rights Edited by Darcy du Toit 2013 ISBN: 978-1-920538-20-0 Pages: viii 380 Print version: Available Electronic version: Free PDF available